PENGEMBANGAN DIRI MAHASISWA UNIVERSITAS HASANUDDIN DALAM KAITANNYA DENGAN LEADERSHIP IDENTITY - Akhbar, Muhammad Noerul; Ridfah, Akhmad; Tamar, Muhammad (Universitas Negeri Makassar, 2018)
The purpose of this study was to describe the self-development of Hasanuddin University students in relation to leadership identity (LI). The LI mapping of Hasanuddin University students is needed because it will have an impact on the pattern of organization and overall student leadership. One factor of LI itself is self-development. This study uses a descriptive qualitative approach. Subjects in this study were three students functionaries of Hasanuddin University. Data was collected through interviews, then analyzed based on content analysis in accordance with the sequences in the qualitative research process. This research succeeded in getting a description of the development of student functionaries. Meanwhile, the leadership identity of student functionaries is in the transition stage from stage three to stage four. Participant describe their relationship with their members as, saw relationships with members as cooperation, respect the values of group members, establish meaningful attachments with others, and see the potential of the group.